The Difference of Work Posture in Musculo-skeletal Disorder Symptoms among Sales Women in the Department Store - Nadrah, Nailatun; Silaban, Gerry; Ashar, Taufik (Indonesian Journal of Medicine, 2018)
Background: Musculoskeletal complaints often occur in saleswomen who do awkward standing during work. Repair of standing position can reduce the risk of musculoskeletal pain. This study aimed to examine the effectiveness of corrective work posture on alleviating musculoskeletal disorder (MSD) symptoms among saleswomen in the department store.Subjects and Method: This was a quasi experiment before and after with no control design conducted in Rantauprapat department store, North Sumatera. A sample of 30 sales women from the department store was selected for this study. The dependent variable was MSD scores as measured by Nordic Body Map (NBM). The independent variables were corrective work posture. The data before and after corrective work posture were compared and tested by t-test.Results: There was a difference between poor and good posture in MSD symptoms among saleswomen in the Department Store. Saleswomen with poor posture had higher MSD symptoms (mean 64.45) than those with good posture (53.39), and it was statistically significant (p= 0.001).Conclusions: Saleswomen with poor posture has higher MSD symptoms than those with good postureKeywords: musculoskeletal disorders, work posture correction, Nordic Body MapCorrespondence:Nailatun Nadrah. Department of Occupational Health and Safety, Faculty of Public Health, Universitas Sumatera, Medan, North Sumatera. Email: nailatunnadrah@gmail.com. Mobile: +6281360661677Indonesian Journal of Medicine (2018), 3(1): 44-48https://doi.org/10.26911/theijmed.2018.03.01.06